Diagnosis and treatment of colorectal tumors: Differences between Japan and the West and future prospects. Issue 1 (11th November 2021) - Saito, Yutaka; Ono, Akiko; García, Victoria Alejandra Jiménez; Mizuguchi, Yasuhiko; Hisada, Izumi; Takamaru, Hiroyuki; Yamada, Masayoshi; Sekiguchi, Masau; Makiguchi, Mai; Sekine, Shigeki; Abe, Seiichiro
Abstract: Dye‐based chromoendoscopy has long been used routinely for endoscopic diagnosis of gastrointestinal tumors including colorectal tumors in Japan. In the West, on the other hand, dye‐based chromoendoscopy was not so commonly used. However, with the development of narrow band imaging (NBI), image‐enhanced endoscopy diagnosis has rapidly increased in the West. The most critical difference between Japan and the West is the histopathological evaluation of the lesions, which determines a major cause of differences in diagnostic and treatment strategies. In the West, intramucosal adenocarcinoma is not diagnosed until the cancer has invaded submucosal layer. In Japan, on the other hand, cancer is mainly diagnosed based on nuclear and structural atypia, and thus intramucosal adenocarcinoma is diagnosed in lesions that correspond to high‐grade adenoma in the West. In the West, since intramucosal carcinoma is not diagnosed by pathology, all benign adenomas are treated by piecemeal endoscopic resection, and only cancer invading the superficial submucosal layer is indicated for endoscopic submucosal dissection (ESD). Because of the risk of lymph node metastasis in the deep submucosal invasion, the European Society of Gastrointestinal Endoscopy and American Society for Gastrointestinal Endoscopy guidelines state that only superficial submucosal cancer is an indication for ESD. Unfortunately, it is impossible to selectively extract only superficial submucosal invasive cancer even with the use of magnified NBI and pit pattern observation. Therefore, we think that pathologists need to diagnose intramucosal adenocarcinoma with the potential to invade the submucosal layer based on the nuclear and structural atypia. Consequently, intramucosal adenocarcinoma and superficial submucosal cancers should be considered for en‐bloc ESD.